Development of Learning Modules Based on Metacognition Approaches to Improve Students' Mathematical Problem Solving Abilities - Murtadha, Ricky; Saragih, Sahat; Amin Fauzi, Kms. Mhd. (Jurnal Perspektif, 2025)
The purpose of this study is: To determine the validity, practicality, and effectiveness of the metacognitive approach-based learning module in improving the mathematical problem-solving abilities of students at MTs Al Washliyah 16 Perbaungan, To analyze the answer process of students at Mts Al Washliyah 16 Perbaungan in solving mathematical problem-solving ability test questions. This research method uses the Four-D Thiagarajan development type of research, the sample of this study was at MTS AL Wasliyah 16 Perbaungan. The results of this study are: Design Based on the results of the research and discussion that have been carried out, it can be concluded that: The metacognitive-based mathematics learning module that has been developed has met the eligibility criteria in terms of material, appearance, interactivity, and ease of use. This eligibility is obtained based on the results of validation by material experts, media experts, as well as the results of limited trials and extensive trials conducted on students. This metacognitive web-based mathematics learning module has proven effective in improving students' mathematical problem-solving abilities. This is indicated by a significant increase in mathematical problem-solving ability scores after students used the developed learning module compared to before using the module.